Pendampingan Pembukuan, Inventarisasi, dan Pelaporan Barang Milik Daerah dalam Upaya Menciptakan Laporan Keuangan Berkualitas di Kabupaten Pinrang - Darmawati, Darmawati; Kusumawati, Andi; Syamsuddin, Syamsuddin; Indrijawati, Aini; Juanda, Indira Syakira Kirana (Prima Abdika: Jurnal Pengabdian Masyarakat, 2024)
The demand for the application of Good Governance (GG) principles in regional financial management emphasizes the importance of transparency and accountability, especially in the management of Regional Property (BMD). The Pinrang District Government faces challenges in preparing BMD reports, such as late reporting, incomplete asset data, and suboptimal recording. This program aims to improve the capability of BMD managers in Pinrang Regency through intensive training and mentoring, in accordance with Permendagri No.47 of 2021. The program implementation methods include lectures, hands-on practice, technical assistance, and evaluation. The materials presented covered BMD bookkeeping, inventory, and reporting, with a focus on using the Simda BMD application to improve report efficiency and accuracy. The evaluation results showed that the program succeeded in improving participants' understanding and skills in BMD management. The resulting outputs include more integrated and quality semesterly BMD reports, as well as an increase in the suitability of asset data with physical conditions in the field. With this success, the program made a real contribution in supporting more transparent, accountable, and regulated regional asset governance, as well as strengthening the capacity of the Pinrang Regency Financial and Revenue Management Agency (BPKPD) in overseeing better regional financial management.